2010
DOI: 10.1583/10-3058.1
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Stent-Graft Disintegration Caused by Cardiac-Induced Aortoiliac Movements

Abstract: We present a 68-year-old man with a 5.8-cm infrarenal abdominal aortic aneurysm who was treated 5 years ago by endovascular placement of a bifurcated Life-Path stent-graft (Edwards Lifesciences, Irvine, CA, USA; Fig- ure, A). Two years later, migration of the right iliac limb (Figure , B) was seen on electrocardiographically-triggered (dynamic) computed tomographic angiography (CTA), which also revealed considerable craniocaudal heartbeat-dependent movement of the aorta (Movie 1). Migration of the limb continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Their values were 0.08 mm with Sylgard 160 and 0.34 mm with Sylgard 170, when considering changes of maximum diameter between 80 and 120 mm Hg. The cyclic motions observed in this study are in better agreement with expected motions at the maximum diameter and to motions overall of most untreated AAA studies (motions of ~ 1.0mm) as is summarized by van Keulen et al [15], though they are less than those reported in Fades et al [44], which showed a mean motion of 3.51 mm prior to endograft treatment. The motions observed (summarized in Table 2) are also in line with what is expected from the observations of Long et al [16] of Ep with the interquartile range of 2.6 X 10"^ Pa to 4.3 x lO' Pa, with a median of 3.4 x lO' Pa.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Their values were 0.08 mm with Sylgard 160 and 0.34 mm with Sylgard 170, when considering changes of maximum diameter between 80 and 120 mm Hg. The cyclic motions observed in this study are in better agreement with expected motions at the maximum diameter and to motions overall of most untreated AAA studies (motions of ~ 1.0mm) as is summarized by van Keulen et al [15], though they are less than those reported in Fades et al [44], which showed a mean motion of 3.51 mm prior to endograft treatment. The motions observed (summarized in Table 2) are also in line with what is expected from the observations of Long et al [16] of Ep with the interquartile range of 2.6 X 10"^ Pa to 4.3 x lO' Pa, with a median of 3.4 x lO' Pa.…”
Section: Discussionsupporting
confidence: 90%
“…which have been summarized by van Keulen et al [15]. Clinical measurements of deformation such as Ep (also called Peterson's or pressure-.strain modulus) also have shown promise in rupture prediction [16].…”
Section: Introductionmentioning
confidence: 99%